2023
DOI: 10.1038/s41598-023-33326-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pandemic-related stress on attentional bias and anxiety in alexithymia during the COVID-19 pandemic

Abstract: The COVID-19 pandemic had negative consequences for mental health, yet it is unknown how and to what extent the psychological outcomes of this stressful event are moderated by individual traits. Alexithymia is a risk factor for psychopathology, and thus likely predicted individual differences in resilience or vulnerability to stressful events during the pandemic. This study explored the moderating role of alexithymia in the relationships of pandemic-related stress with anxiety levels and attentional bias. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 117 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…However, stress is only one of the risks that cause individual anxiety and depression, and other factors (e.g. anxiety and social support) have a significant impact on an individual’s level of anxiety and depression [ 47 , 48 ]. Stress, anxiety, and depression are interrelated and independent.…”
Section: Discussionmentioning
confidence: 99%
“…However, stress is only one of the risks that cause individual anxiety and depression, and other factors (e.g. anxiety and social support) have a significant impact on an individual’s level of anxiety and depression [ 47 , 48 ]. Stress, anxiety, and depression are interrelated and independent.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DIF, representing difficulties in identifying one's own emotions, has been linked to insomnia (Montoro et al., 2016 ). Concerning EOT, studies have demonstrated that a greater inclination toward EOT, where individuals focus on external events rather than their internal emotional experiences, is associated with insomnia (Lee & Lee, 2023 ). This cognitive style may lead to heightened preoccupation with external stressors, making it difficult for individuals to disengage from worrisome thoughts and attain restful sleep (Greene et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%